ENTREPRENEURIAL ECOSYSTEMS AND MSME COMPETITIVENESS: LINKING INSTITUTIONS, NETWORKS, AND LOCAL CAPABILITIES - Rama Tresnadi; Faisal Matriadi (Journal of Jabar Economic Society Networking Forum, 2024)
This conceptual paper develops an integrative framework for entrepreneurial ecosystem capability in micro, small, and medium enterprises (MSMEs). Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial-ecosystem literature, the paper explains how institutional support, network diversity, local knowledge, market access, and enterprise learning can be organized into practical managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The analysis proposes a staged cycle of diagnosis, experimentation, evidence review, governance, and resource reconfiguration. It further identifies implications for owner-managers, support institutions, and future empirical research. The framework emphasizes that capability development should be proportionate to enterprise constraints and evaluated through decision quality, learning, resilience, and business outcomes rather than adoption indicators alone.